Phytochemical screening and evaluating allelopathic potential of crude extracts from Lantana camara (L.) leaves and Wedelia trilobata (L.) on seed germination - Trương Quốc Tất; Võ Nhựt Huế; Nguyễn Huỳnh Như Ý; Nguyễn Duy Khánh (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ, 2024)
Lantana camara (L.) and Wedelia trilobata (L.) are wild and strong invasive plants. The aims of this study are to screen phytochemical profiles and evaluate the allelopathic ability of crude extracts on Echinochloa crus-galli (L.), Lactuca sativa (L.) and Raphanus sativus (L.) seed germination in vitro condition. The results showed that, two ethanol crude extracts revealed the high presence of the chemical compositions such as phenolic, flavonoid và alkaloid. The W. trilobata (L.) extract inhibited seed germination higher than the L. camara (L.) leaves extract. At the concentration of 5 mg/mL, the crude extract from W. trilobata (L.) showed inhibition on seed germination of E. crus-galli (L.), L. sativa (L.), and R. sativus (L.) with 84.83%, 82.59%, and 96.57%, respectively. Therefore, W. trilobata could be seen as a potential plant for research on allelochemicals.